EFFECTS OF SOIL SALT CONCENTRATION ON nirS AND nosZ GENES DIVERSITY OF PADDY SOIL DENITRIFYING BACTERIA - Yuexia Ding; Jieheng He; Qun Wu; Dejun Li; Guangchao Liu; Jieshen Liao; Hongkai Zhou (Journal of Animal and Plant Sciences, 2023)
To further study saline-alkali soil cultivation, the terminal-restriction fragment length polymorphism (T-RFLP) was used to analyze the effects of different salt concentrations on the denitrification functional genes nirS and nosZ after collecting different soil samples and extracting total soil DNA. The results showed that the variation range of nirS gene abundance was concentrated in 14 segments, the nosZ gene abundance was concentrated in 9 segments. The abundance of nirS gene in paddy soil of different concentrations was higher than nosZ, and the activity of the nirS gene was higher. Diversity index analysis showed that sample Ⅰ was significantly different from Ⅲ and Ⅴ in the Shannon index of the nirS. Sample Ⅰ and Ⅳ were significantly different from Ⅲ in Simpson index. Except for the significant difference between Ⅲ and Ⅰ, Ⅱ, Ⅳ, and Ⅴ, there was no difference between the other four samples significant in Pielou index. The difference between sampl Ⅰ and Ⅴ was extremely significant in Brillouin index. The Shannon index, Simpson index and Pielou index of nosZ gene were not significantly different, sample Ⅱ and Ⅲ, Ⅳ, Ⅴ were significantly different in Brillouin index. The diversity of nirS gene was more affected by the salt concentration, and the nirS gene was more widely distributed than nosZ in soil with different salt concentrations. It indicated that nirS -mediated nitrite reductase played an important role in salinity affected soil environment.
Keywords: Denitrifying bacteria; Functional denitrification gene; Salt concentration; Diversity; Soil